Dynamics of nasopharyngeal tract phageome and association with disease severity and age of patients during three waves of COVID‐19. Issue 11 (25th July 2022) - Ferravante, Carlo; Arslan‐Gatz, Berin S.; Dell'Annunziata, Federica; Palumbo, Domenico; Lamberti, Jessica; Alexandrova, Elena; Di Rosa, Domenico; Strianese, Oriana; Giordano, Alessandro; Palo, Luigi; Giurato, Giorgio; Salzano, Francesco A.; et al.
Abstract: In December 2019, several patients were hospitalized and diagnosed with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection, which subsequently led to a global pandemic. To date, there are no studies evaluating the relationship between the respiratory phageome and the SARS‐CoV‐2 infection. The current study investigated the phageome profiles in the nasopharyngeal swabs collected from 55 patients during the three different waves of coronavirus disease 2019 (COVID‐19) in the Campania Region (Southern Italy). Data obtained from the taxonomic profiling show that phage families belonging to the order Caudovirales have a high abundance in the patient samples. Moreover, the severity of the COVID‐19 infection seems to be correlated with the phage abundance.